(untitled) - H Johnson (Oxford, New York, 1966)
This book attempts to serve as a reference book on American history. Most of the articles in it are summaries of lives, events, and places significant in the founding anf growth of the nation. It gives attention to social, political, and labor movements, the observations of travelers, both foreign and domestic, and includes the fields of art, science, commerce, literature, education, and law. There are also articles dealing with sports and entertainment. The matter of proportion has been an especially acute problem. The longest articles on persons, those for example on Washington, Franklin, Jefferson, and Lincoln, do not exceed 2.00 words. Such events as the War of Independence, the Civil War, and both World Wars are of similar proportion. Cross references, indicated in the articles by small capitals. The longer articles are concluded with reference to the most recent authoritative bibliographical sources. In general, living persons are briefly treated. tables provide quick reference to the names and dates of persons who have held high office, such as cabinet members and Justices of the Supreme Court. The texts of the Constitution and its Amendments are given at the end of the book
Keywords: america - history - encyclopedias